Regional differences, distribution dynamics, and convergence of multidimensional food security levels in the Yangtze river economic belt - Jing Cheng; Yaning Liu (PLoS ONE, 2026)
Food security is a key foundation for the Yangtze River Economic Belt’s high-quality development. Using a multidimensional food security evaluation framework that encompasses quantity, quality, ecology, and capacity, this paper analyzes 131 prefecture-level cities from 2009 to 2022 through Gini coefficient decomposition, kernel density estimation, and convergence modeling. The study reveals an overall steady rise in food security, characterized by shrinking but still significant regional disparities and increasing coordination. The region’s distribution dynamics exhibit an olive-shaped structure, characterized by being “big in the middle and small at the ends.” Further analysis reveals that the midstream region converges the fastest due to policy alignment and technology diffusion, whereas the downstream region, hindered by urbanization and market segmentation, experiences the “high β coefficient - low convergence speed” paradox. The key drivers of divergent convergence paths are policy heterogeneity and misallocated resources. Based on these findings, differentiated governance strategies are proposed to promote integrated food security and ecological protection.